2019
DOI: 10.1213/xaa.0000000000001129
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Thromboembolic Events in Oncology Patients Receiving Intraoperative Tranexamic Acid During Orthopedic Surgery: A Retrospective Review at a Comprehensive Cancer Center

Abstract: Despite an abundance of evidence, routine perioperative antifibrinolytics have been avoided in oncology patients due to concern of thrombosis when given to patients with a preexisting hypercoagulable state. We present a retrospective review of 104 patients with an oncologic diagnosis who received intraoperative tranexamic acid during orthopedic surgery. Overall, complication rates were low, including deep vein thrombosis (1.0%), pulmonary embolism (4.8%), stroke (0%), and myocardial infarction (0%). This preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It should be noted that this study included 90 patients of heterogeneous age groups that were treated for either primary bone sarcoma or bone metastasis of the proximal femur, distal femur, and proximal tibia. Ackerman et al 20 investigated the effect of TXA on thromboembolic events in orthopaedic oncology surgery and concluded that TXA was safe to use in these patients. However, this study included both patients with primary sarcomas and metastases involving different anatomic regions.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this study included 90 patients of heterogeneous age groups that were treated for either primary bone sarcoma or bone metastasis of the proximal femur, distal femur, and proximal tibia. Ackerman et al 20 investigated the effect of TXA on thromboembolic events in orthopaedic oncology surgery and concluded that TXA was safe to use in these patients. However, this study included both patients with primary sarcomas and metastases involving different anatomic regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence suggests that the use of TA may be considered safe in cancer patients, contrary to previous beliefs (27).…”
Section: Discussionmentioning
confidence: 70%
“…Focusing on orthopaedic and oncologic surgery, Ackerman et al [30] reported 104 oncological cases treated with perioperative intravenous injections of 15mg/kg of TXA during orthopaedic procedures. In their experience the incidence of major complications was relatively low (17%) and significant postoperative bleeding and hemodynamic instability were extremely uncommon (3%).…”
Section: Discussionmentioning
confidence: 99%